Postmodern Portfolio Theory - Lovás, Branislav (2018)
Submitted thesis focuses on the theory and practice of portfolio optimization and management. Theoretical section deals with modern portfolio theory in Markowitz's interpretation, which is afterwards confronted with empirical realities regarding behavior of financial returns and securities markets. In response to these shortcomings, the postmodern portfolio theory is introduced, whereas individual subchapters focus on selected areas of this theory. Several alternative approaches to portfolio optimization are presented within each one of these sections. Subsequently alternatives to capital asset pricing model (CAPM) are also presented, that being in form of multi-factor fundamental models and extensions to CAPM utilizing higher moments or only downside returns. Theoretical part is concluded with the overview of traditional and less commonly used indicators of portfolio performance. Practical part consists of implementation of presented models in R scripting language. Focal point of practical section is comparison of individual methods on model portfolios.